2008
DOI: 10.1529/biophysj.107.125054
|View full text |Cite
|
Sign up to set email alerts
|

The β-Strand-Loop-β-Strand Conformation Is Marginally Populated in β2-Microglobulin (20–41) Peptide in Solution as Revealed by Replica Exchange Molecular Dynamics Simulations

Abstract: Solid-state NMR study shows that the 22-residue K3 peptide (Ser(20)-Lys(41)) from beta(2)-microglobulin (beta(2)m) adopts a beta-strand-loop-beta-strand conformation in its fibril state. Residue Pro(32) has a trans conformation in the fibril state of the peptide, while it adopts a cis conformation in the native state of full-length beta(2)m. To get insights into the structural properties of the K3 peptide, and determine whether the strand-loop-strand conformation is encoded at the monomeric level, we run all-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…A popular workaround to overcome the limitations of classical MD is the replica exchange (RE) method ( Nishino et al, 2005 ; Liang et al, 2007 , 2008 ; Wei et al, 2008 ; De Simone and Derreumaux, 2010 ; Nishikawa et al, 2019 ), in which several MD trajectories (the so called replicas) run in parallel at different temperatures, and moves between adjacent replicas are attempted based on a Monte Carlo Metropolis rule ( Nishino et al, 2005 ; Liang et al, 2007 , 2008 ; Wei et al, 2008 ; De Simone and Derreumaux, 2010 ; Nishikawa et al, 2019 ). By limiting trapping in local energy minima, RE allows equilibrium sampling of the conformational landscape.…”
Section: Computational Models and Techniques Used To Study β2m Aggregmentioning
confidence: 99%
“…A popular workaround to overcome the limitations of classical MD is the replica exchange (RE) method ( Nishino et al, 2005 ; Liang et al, 2007 , 2008 ; Wei et al, 2008 ; De Simone and Derreumaux, 2010 ; Nishikawa et al, 2019 ), in which several MD trajectories (the so called replicas) run in parallel at different temperatures, and moves between adjacent replicas are attempted based on a Monte Carlo Metropolis rule ( Nishino et al, 2005 ; Liang et al, 2007 , 2008 ; Wei et al, 2008 ; De Simone and Derreumaux, 2010 ; Nishikawa et al, 2019 ). By limiting trapping in local energy minima, RE allows equilibrium sampling of the conformational landscape.…”
Section: Computational Models and Techniques Used To Study β2m Aggregmentioning
confidence: 99%
“…However, no stable K3 oligomers with either single-or double-layered annular features were observed in solution. Structural analysis using replica exchange MD revealed that a β-hairpin structure is predicted for the β 2 m fragment (83–99),28 while the β-strand-turn-β-strand motif is marginally populated in solution 29…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, using both experiments and bioinformatics, it is understood that the location of both charged and hydrophobic amino acids6 and the side chains details7 are critical in accelerating or slowing down the kinetics, and eventually preventing fibril formation. Even though recent Monte Carlo8 and molecular dynamics simulations9–12 have suggested that amyloid aggregation pathways are sequence‐dependent, the full impact of hydrophobic variation on both the thermodynamics and dynamics of aggregation remains to be determined.…”
Section: Introductionmentioning
confidence: 99%